2017
DOI: 10.1108/ajim-08-2016-0141
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of dementia

Abstract: Article:Harland, J., Bath, P.A. orcid.org/0000-0002-6310-7396, Wainwright, A. et al. (1 more author) (2017) Making sense of dementia: a phenomenographic study of the information behaviours of people diagnosed with dementia. Aslib Journal of Information Management, 69 (3). pp. 261-277. ISSN 2050-3806 https://doi.org/10.1108/AJIM-08-2016-0141 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(63 reference statements)
2
4
0
Order By: Relevance
“…Although our research validates the importance of support groups (and provides evidence for their role in filling physiological, social, and emotional information needs), our findings refute this claim of disinterest. Our findings are more aligned with the recent Harland et al [10] study, which highlights the interests of some people with dementia to seek information 4 weeks after diagnosis, whereas others avoided it as they felt they could not affect their situation [10]. Similarly, we found that some individuals, such as Velma, practiced information avoidance for up to 6 months after diagnosis.…”
Section: Comparison With Prior Worksupporting
confidence: 89%
See 4 more Smart Citations
“…Although our research validates the importance of support groups (and provides evidence for their role in filling physiological, social, and emotional information needs), our findings refute this claim of disinterest. Our findings are more aligned with the recent Harland et al [10] study, which highlights the interests of some people with dementia to seek information 4 weeks after diagnosis, whereas others avoided it as they felt they could not affect their situation [10]. Similarly, we found that some individuals, such as Velma, practiced information avoidance for up to 6 months after diagnosis.…”
Section: Comparison With Prior Worksupporting
confidence: 89%
“…Similarly, we found that some individuals, such as Velma, practiced information avoidance for up to 6 months after diagnosis. Some participants' justification for information avoidance was because they felt emotionally "numb" (Velma) rather than powerless to affect their situation, as reported in the study by Harland et al [10], and even reported the decisions to engage in various information behaviors, including actively seeking dementia information later in their lives. Because of our semistructured interviews with 16 participants with dementia recruited through convenience sampling, we were able to discover the transitions that many participants underwent in their information behavior.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 3 more Smart Citations